2020
DOI: 10.1016/j.jeconom.2019.12.015
|View full text |Cite
|
Sign up to set email alerts
|

A coupled component DCS-EGARCH model for intraday and overnight volatility

Abstract: We propose a semi-parametric coupled component exponential GARCH model for intraday and overnight returns that allows the two series to have different dynamical properties. We adopt a dynamic conditional score model with t-distributed innovations that captures the very heavy tails of overnight returns. We propose a several-step estimation procedure that captures the nonparametric slowly moving components by kernel estimation and the dynamic parameters by maximum likelihood. We establish the consistency, asympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…This paper deviates from previous approaches in that we no longer treat the proportionality parameter c as a static parameter. This is in line with findings of Ahoniemi et al (2015), Linton and Wu (2020), among others, who show that the daytime and overnight volatility processes have their own dynamics, and that, hence, the ratio c might not be constant over time. Instead of a static c, we propose a dynamic parameter c t that we endow with the score-driven (GAS) dynamics of Creal et al (2013); see also Harvey (2013).…”
Section: Modeling Frameworksupporting
confidence: 92%
See 2 more Smart Citations
“…This paper deviates from previous approaches in that we no longer treat the proportionality parameter c as a static parameter. This is in line with findings of Ahoniemi et al (2015), Linton and Wu (2020), among others, who show that the daytime and overnight volatility processes have their own dynamics, and that, hence, the ratio c might not be constant over time. Instead of a static c, we propose a dynamic parameter c t that we endow with the score-driven (GAS) dynamics of Creal et al (2013); see also Harvey (2013).…”
Section: Modeling Frameworksupporting
confidence: 92%
“…For many stocks, our model improves significantly upon the HEAVY model of Shephard and Sheppard (2010) or a model with a static volatility ratio. We also confirm Linton and Wu (2020) by showing that modeling the overnight volatility separately leads to low values of the degrees of freedom parameter, with subsequent potential problems for the existence of sufficient moments (see also Berkman et al, 2012).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…The non-linear update in Equation ( 11) is robust to fat-tails since it downweights volatility estimates when extreme price movements occur. For this reason, it has been extensively applied in the finance and economic literature; see also Creal et al (2011), Linton and Wu (2020). The score of a zero return in the Beta-t-EGARCH reduces to u t = −1.…”
Section: Estimation and Filteringmentioning
confidence: 99%
“…Blanc et al (2014) applied a quadratic ARCH framework and found that the intraday return and overnight return behave completely differently as expected. Linton and Wu (2020) proposed a semiparametric coupled component exponential GARCH model for intraday and overnight returns, with t distribution innovation that captures the fat tail of overnight return.…”
Section: Introductionmentioning
confidence: 99%